Lo-fi Freedoms and the Anti-Aesthetic Photograph - Nepomuceno, Rex Sandro M. (Philippine Humanities Review, 2025)
This visual rhetorical critique accounts for the cultural positionality of “anti-aesthetic” photographs. The digital photographic projects Picture lang and Mga sulat sa daan are taken as cases of contemporary visual practices that interrupt and resist aesthetic values. I engage them through an ontological approach by analyzing the rhetoricity of images within the modalities of visual practice. This entails encountering photographs as what Kevin Michael DeLuca refers to as image events— images that produce realities rather than just represent them. To locate eventfulness is to identify how images facilitate alternative ways of seeing from which new viewing subjects can emerge. I utilize contemporary modalities of glances, speed, and distraction while reworking Roland Barthes’ ideas on the rhetoric of images to argue for the rhetoricity of foregrounding the denotative. Denotations work by defamiliarizing the viewer and recalibrating their sense of value towards images. I also argue that the anti-aesthetics function through a multimodality of performances. Performances of orality and silences imbue image events with sonic qualities and imaginaries while their liminality challenges notions of homogeneity in favor of instability and potentiality. To delineate its political effects, reproducibility and circulation are forwarded as crucial performative qualities that allow anti-aesthetic photos to evade commodity status and undergo transformations in their form and function. However, the anti-aesthetics’ resistant positionality is not fixed. It can still acquire value and gain currency within aesthetic industries. But these “failures” of the anti-aesthetic do not equate to its impossibility. The anti-aesthetic is still a valid category of critique as demonstrated by its capability to rhetorically transform our understanding of aesthetic value and ways of seeing, feeling, and understanding. Thus, the freedoms afforded by these anti-aesthetic projects are likewise in low-fidelity— offering brief glances of complex futures.